2019
DOI: 10.1159/000504135
|View full text |Cite|
|
Sign up to set email alerts
|

Absence of Testicular Adrenal Rest Tumors in Newborns, Infants, and Toddlers with Classical Congenital Adrenal Hyperplasia

Abstract: <b><i>Introduction:</i></b> Testicular adrenal rest tumors (TART) are a known consequence for males with classical congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency. TART are associated with potential infertility in adults. However, little is known about TART in very young males with CAH. <b><i>Objective:</i></b> We assessed the presence of TART in newborn, infant, and toddler males with classical CAH via scrotal ultrasound. <b><i>… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…TARTs occur in up to 86% of males with classic CAH [3]. In children, the reported prevalence is 21–24% [7, 8] and though rare [9, 10], TARTs have been documented in boys as young as age 4 [11]. TARTs arise at the rete testis (stage 1) and are not palpable until stages 3 or 4 when fibrosis and lymphocytic infiltration are present [3].…”
Section: Discussionmentioning
confidence: 99%
“…TARTs occur in up to 86% of males with classic CAH [3]. In children, the reported prevalence is 21–24% [7, 8] and though rare [9, 10], TARTs have been documented in boys as young as age 4 [11]. TARTs arise at the rete testis (stage 1) and are not palpable until stages 3 or 4 when fibrosis and lymphocytic infiltration are present [3].…”
Section: Discussionmentioning
confidence: 99%
“… 3 - 7 Although, TART was not detected in neonates or toddlers, a single study reported the presence of TART in young children with CAH as the youngest affected patient was 1.8 year old. 9 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] Although, TART was not detected in neonates or toddlers, a single study reported the presence of TART in young children with CAH as the youngest affected patient was 1.8 year old. 9,21 It was suggested that TART prevalence increases with age, as the nature of the disease would require time to develop. 22 In a 6-year follow-up study of patients with CAH aged 3-23 years, the prevalence of TARTs increased from 41% to 66% in those patients during the follow up, with 16 times greater chance of TART development due to poor control mostly at pubertal age.…”
Section: Management Of Children With Cahmentioning
confidence: 99%
“…The mechanism of ART formation still has not yet been fully elucidated. Kim et al [ 4 ] mentioned that these tumors may arise from ectopic migration of residual adrenal cortex cells into the developing gonads because of the connection between the adrenal glands and gonads during embryonic development. Claahsen-van der Grinten et al [ 5 ] suggested that defective primary sex cord regression, including all aberrant adrenal cells, during gonad development may be a causative factor in OART development.…”
Section: Discussionmentioning
confidence: 99%